Corporate investment, debt and liquidity choices in the light of financial constraints and hedging needs - Christina E. Bannier; Carolin Schürg (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
We examine firms' simultaneous choice of investment, debt financing and liquidity in a large sample of US corporates between 1980 and 2014. We partition the sample according to the firms' financial constraints and their needs to hedge against future shortfalls in operating income. In contrast to earlier work, our joint estimation approach shows that cash flows affect the corporate decisions of unconstrained firms more strongly than those of constrained firms. Investment-cash flow sensitivities are particularly intense for unconstrained firms with high hedging needs. Investment opportunities (as proxied by Q), however, play a larger role for constrained firms with the effects being strongest in case of low hedging needs. Interestingly, constrained firms with low hedging needs are found to employ more debt to finance their investment opportunities and build up significant cash holdings at the same time. Our results hence indicate overinvestment behavior for unconstrained firms but no underinvestment for constrained firms if they have low hedging needs.
urn:nbn:de:hebis:30:3-382797
Keywords: G31; G32; 330; cash flow sensitivity; investment; debt issuance; cash holdings